Environmental Factors With Respiratory Tract Infections in Toddlers in the Work Area of the Lima Puluh Health Center: Faktor Lingkungan Dengan Kejadian Ispa Pada Balita Di Wilayah Kerja Puskesmas Lima Puluh - Ratri Putri Bestari; Suharmadji Suharmadji; Novita Lusiana; Denai Wahyuni; Yeyen Gumayesti (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Acute respiratory infection (ARI) is an acute respiratory infection that attacks the throat, nose and lungs that lasts approximately 14 days, Ari regarding the structure of the channel above the larynx, data on Ari disease in toddlers in Pekanbaru city show that the highest prevalence in Puskesmas fifty with a prevalence rate of 6.69% per 100 toddlers in 2020. This research is quantitative analytic with Case Control design. The study was conducted in January-July in the second quarter of 2022 in the Working Area of Puskemas Lima Puluh Kota Pekanbaru, with a population of 4,946 toddlers and a sample of 135 which was divided into 45 cases and 90 controls. This study uses Simple Random Sampling technique. Data analysis methods include univariate and bivariate analysis, using chi-square test. The results showed that the variables associated are ventilation (OR=3.294 95% CI 1.553-6.989), exposure to cigarette smoke (or=3.436 95% CI 1.575-7.504), occupancy density (or=4.529 95% CI 2.113-9.710), environmental sanitation (or=2.896 95% CI 1.359-6.169). Suggestions from researchers are rekrontuksi ventilation / open the window periodically, the manufacture of smoking corner in the surrounding environment, isolation room for family members affected by the disease, rekrontuksi base of the building at risk of becoming the development of bacterial culture/paint water repellent against risky building materials such as wood.